Effect of porous medium and nanoparticles presences in a counter-current triple-tube composite porous/nano-PCM system. (25th February 2020) - Li, Zhixiong; Shahsavar, Amin; Al-Rashed, Abdullah A.A.A.; Talebizadehsardari, Pouyan
Highlights: Simultaneous usage of geometry modification, nanoparticles and porous medium. Study on the effect of the flow direction of HTF in a triple-tube LHS unit. 25.9/28.2% lower melting/solidification time by 5% nanoparticles addition. 83.7/88.2% lower melting/solidification time by 95% porous metal foam addition. Negligible effect of adding nanoparticles in the presence of porous medium. Abstract: To solve the problem of low thermal conductivity of phase change materials (PCMs), three different methods including geometry modification, adding nanoparticles and metal foam are studied in a triple-tube latent heat storage system (LHS). PCM is enclosed in the middle tube while water passes through the inner and outer tubes as the heat transfer fluid (HTF). Different nanoparticles concentrations and metal foam porosities are examined. Different HTF flow directions in the inner and outer tubes related to the gravity direction are assessed. The results show the advantage of the system with counter-current flow of the HTF when the HTF flow in the outer tube is in the gravity direction. By adding 5% copper nanoparticles, the melting/solidification time reduces by 25.9/28.2%. By adding a 95% porous metal foam, the melting/solidification time reduces by 83.7/88.2% showing the advantage of adding a metal foam compared with adding nanoparticles. Increasing the volume fraction of nanoparticles or reducing the porosity of the metal foam reduce the melting/solidification time. Simultaneous usage of the nanoparticles and metal foam show that in the presence of metal foam, the effect of adding nanoparticles is almost negligible. For the porous/nano-PCM case with 95% porosity of the metal foam and 5% volume fraction of nanoparticles, the melting/solidification time reduces by 84.2/88.8% compared with the pure PCM system. This paper provides a clear and comprehensive vision of the simultaneous effects of different heat transfer enhancement methods inside the PCM in triple-tube LHS systems.